EMOTIONAL INTELLIGENCE AND LEADERSHIP STYLE - Lukman@Zawawi, Mohamad; Norzulaika, Alias; Kamal, M.Y. (2018)
The purpose of this study was to examine the level of emotional intelligence among deans in Universiti Teknologi Mara (UiTM), to identify the most preferred leadership style by deans in UiTM and lastly to investigate the relationship between emotional intelligence and leadership style among deans in UiTM. Six faculties were selected based on applied science and social science disciplines. Data were collected using questionnaire and interview techniques. Data were analyzed using descriptive and inferential statistics. The findings revealed that the level of emotional intelligence was at the high level among deans of six selected faculties. In addition, findings indicated that most preferred leadership style by deans in UiTM was transformational leadership style perceived by lecturers as respondents. Lastly, findings indicated transformational leadership style was scored (0.34) slightly higher compared to transactional leadership style (0.22) and both dimensions were having the significant relationship between emotional intelligence among deans in UiTM. Overall, the findings of this study have implications for the role of deans, lecturers, and administrators in the way to enhance positive climate. Based on the findings, this study also provides recommendations for improvement of practices and future research